The Fiqh of Hisab-Ru’ya in the Twentieth Century Indonesia: Study on the Thoughts of Hamka, Hasbi Ash-Shiddieqy, and Moenawar Chalil about the Unification of Hijri Calendar - Marwadi Marwadi; Rina Heriyanti; Farah Nuril Izza (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2023)
Fiqh discourses regarding differences in methods and criteria (hisab and ru’ya) for determining the beginning of the Hijri months are still being debated among Muslims in Indonesia. Until now, there is no Hijri calendar that applies globally. The existing Islamic calendar is a local or regional calendar. The absence of a unified Hijri calendar often causes confusion in setting dates in Muslim society, and this makes Muslim intellectuals continue to study it. The idea of creating a unified Hijri calendar in Indonesia was originally raised by Hamka, Muhammad Hasbi Ash-Shiddieqy, and Moenawar Chalil. This research explores how the Hijri calendar is unified according to their opinions. This study is a qualitative research with a socio-historical and hermeneutic approach. Data collection uses the documentation method with the content analysis model. The results of this study indicate that Hamka believes that there needs to be a unified result between the hisab and the ru’ya methods, so that the Hijri calendar, especially the beginning of Ramadan and Shawwal, can become a fixed date. Meanwhile, Hasbi offers the idea that to overcome the differences in the beginning of Ramadan and Shawwal one must use the ru’yat method with global matla’. Meanwhile, Moenawar Chalil believes that the preparation of the Hijri calendar in Indonesia can only use the hisab method. These three ideas can be a solution in an effort to achieve uniformity of the Hijri calendar in Indonesia.